Downstairs drivers ‐ root herbivores shape communities of above‐ground herbivores and natural enemies via changes in plant nutrients. (14th March 2013) - Johnson, Scott N.; Mitchell, Carolyn; McNicol, James W.; Thompson, Jacqueline; Karley, Alison J.
Summary: Terrestrial food webs are woven from complex interactions, often underpinned by plant‐mediated interactions between herbivores and higher trophic groups. Below‐ and above‐ground herbivores can influence one another via induced changes to a shared host plant, potentially shaping the wider community. However, empirical evidence linking laboratory observations to natural field populations has so far been elusive. This study investigated how root‐feeding weevils ( Otiorhynchus sulcatus ) influence different feeding guilds of herbivore (phloem‐feeding aphids, Cryptomyzus galeopsidis, and leaf‐chewing sawflies, Nematus olfaciens ) in both controlled and field conditions. We hypothesized that root herbivore‐induced changes in plant nutrients (C, N, P and amino acids) and defensive compounds (phenolics) would underpin the interactions between root and foliar herbivores, and ultimately populations of natural enemies of the foliar herbivores in the field. Weevils increased field populations of aphids by ca. 700%, which was followed by an increase in the abundance of aphid natural enemies. Weevils increased the proportion of foliar essential amino acids, and this change was positively correlated with aphid abundance, which increased by 90% on plants with weevils in controlled experiments. In contrast, sawfly populations were 77% smaller during mid‐June and adult emergence delayed by >14 days on plants with weevils. In controlled experiments, weevils impaired sawfly growth by 18%, which correlated with 35% reductions in leaf phosphorus caused by root herbivory, a previously unreported mechanism for above‐ground–below‐ground herbivore interactions. This represents a clear demonstration of root herbivores affecting foliar herbivore community composition and natural enemy abundance in the field via two distinct plant‐mediated nutritional mechanisms. Aphid populations, in particular, were initially driven by bottom‐up effects (i.e. plant‐mediated effects of root herbivory), but consequent increases in natural enemies triggered top‐down regulation. Abstract : This is a clear demonstration of root herbivores affecting foliar herbivore community composition and natural enemy abundance in the field via two distinct plant‐mediated nutritional mechanisms. Aphid populations, in particular, are initially driven by bottom‐up effects (i.e. plant‐mediated effects of root herbivory), but consequent increases in natural enemies trigger top‐down regulation.